INTEGRATIVE LEARNING APPROACH IN ESP/ELP: Theoretical framework of intradisciplinary, multidisciplinary, interdisciplinary, and transdisciplinary integration: Intradisciplinary, Multidisciplinary, Interdisciplinary, and Transdisciplinary Aspects of ELP/LE Instruction for Academic and Professional Purposes - Ignjatovic, Gordana (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2020)
The vibrant expansion of English for Specific Purposes (ESP) has engendered multiple ESP varieties, including English for Legal Purposes (ELP) or Legal English (LE). Due to the multidimensional nature, intricate structure and ample functions of ESP instruction, this article discusses the integrated communicative learning approach to ESP curriculum/syllabus design in the context of ELP/LE instruction for academic/professional purposes. The research is rooted in the Integrated Curriculum Model, which offers a conceptual framework for designing highly meaningful and efficient integrated learning experiences in different educational contexts. This integrated approach entails an array of intrinsically correlated linguistic, methodological, pedagogical, psychological and discipline-specific dimensions, which illustrate the intradisciplinary, multidisciplinary, interdisciplinary and transdisciplinary aspects of ELP/LE instruction. The analysis of distinctive aspects of this approach is substantiated by relevant theoretical framework and examples from ELP/LE teaching practice. The paper aims to contribute to a better understanding of complexities and challenges encountered in ELP/LE curriculum/syllabus design, particularly in terms of striking the right balance between the requisite communication competences and ESP-specific pedagogy, for the purpose of facilitating an authentic, meaningful and methodologically sound instruction in line with the discourse community needs. The author urges for more extensive collaboration and joint action of relevant stakeholders in developing integrated law-and-language programs, courses and projects for academic/professional purposes. The synergy of intradisciplinary, multidisciplinary and interdisciplinary perspectives would be a valuable asset not only in terms of promoting quality legal education and language learning but also in terms of introducing the much-needed holistic approach to authentic learning for personal growth and professional development in the real-world. Such collaboration would ultimately contribute to promoting the transdisciplinary aspects of education envisaged in the framework of global competences and 21st century transferable life skills.
Keywords: ESP; ELP; Legal English; integrative learning; integrated curriculum; authentic learning